PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN KOMUNIKASI TERHADAP KINERJA APARATUR SERTA DAMPAKNYA TERHADAP KUALITAS PELAYANAN PUBLIK - Rizki Pradina Nugraha; Lalan Soeherlan S; Aceng Jarkasih (Universitas Majalengka, 2020)
The performance of public services has a huge influence on the quality of people's lives. The factors that influence public services in this study were identified from the aspects of employee performance, participatory communication and leadership. This type of research used in this research is descriptive verification research. Data collection techniques in this study using survey techniques and data sources in this study are primary and secondary data. The data analysis technique in this study used the path analysis method. The results of descriptive research indicate that participatory leadership, communication, employee performance and service quality are in the sufficient category, so it is necessary to increase their role in order to improve the quality of public services. The results of hypothesis testing have proven that there is an influence between participatory leadership style and communication, both partially and simultaneously, which have a positive effect on employee performance. The results of other hypothesis testing prove that employee performance has a positive and significant effect on the quality of public services